Mass Media and Social Distancing Regulations to Prevent the Spread of the Covid-19 Virus Outbreak in Indonesia (Journal of Creativity Student, 2022)
The current outbreak of the corona virus is becoming increasingly worrisome. More and more people became infected with the corona virus, with some even succumbing to their illness and dying as a result of the virus's spread. Today, social media is a popular means of communicating outside traditional means. In order to prevent the spread of this new disease, I'd like to share my experiences as someone who has been infected with the corona virus, as well as to warn others to stay at home and take care of themselves in order to avoid contracting the sickness. Descriptive qualitative research is employed in this study. It is the goal of this study to educate community members and millennial youth with information and an overview so that they can pay more attention to social ties in society and avoid societal changes as a result of false news causing undue worry. According to the study's findings, the community's usage of social media and other online tools has increased its members' access to information. A large false news campaign about social isolation preceded this, despite the government's call to heed the recommendations relating to social isolation.